PENGEMBANGAN MODUL PEMBELAJARAN MATEMATIKA DENGAN STRATEGI PQ4R UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF DAN KEMANDIRIAN BELAJAR SISWA SMA - Herlin Novalia; Sri Hastuti Noer (Universitas Sultan Ageng Tirtayasa, 2019)
This research is a research development that aims to find out the mathematics module development model that using PQ4R strategy and observing the improvement of creative thinking skills and self-regulated learning by using mathematics learning module and applying PQ4R strategy. The subjects of this research were the students of grade XI at SMAN 6 Bandar Lampung. The preliminary results study shows that there is a need in order to develop the learning modules. The modules organization and development is done by compiling the draft of modules and all its components, based on teaching materials preparation guidelines. Mathematical modules for polynomials study in the grade XI consist of the beginning, core, and end. The validation results show that the module has met the media and material feasibility standards. The first trial shows a very good result. These research test results are in the form of mathematics learning modules on polynomials. The research data was obtained through instruments of creative thinking skills and self-regulated learning scale. Data analysis of this research uses proportion test with SPSS program. The proportion test results towards the effectiveness of modules usage show the students have met the minimum completeness criteria in the creative thinking skills and self-regulated learning. According to research analysis results of the study, the student’s creative thinking and self-regulated learning had been increasing after using mathematics learning module using the PQ4R strategy. Keywords: thinking creatively, module, self-regulated learning